URGENCY OF THE RENEWAL OF CRIMINAL LAW POLICIES IN AN EFFORT TO PROTECT CHILD VICTIMS OF SEXUAL VIOLENCE - Syaiful Asmi Hasibuan (RADJA PUBLIKA, 2025)
Protection efforts for children who are victims of sexual violence must be carried out ongoing so that their welfare is maintained, because children are important assets for the progress of a nation and the country. One protection of children by overcoming crime or violence by giving punishment in a criminal form to irresponsible parties. Determination of the type of punishment and how to apply is very relating to criminal law policies. Criminal law policy is a systemic process in the reduction in criminal actions using criminal law facilities, including the renewal of criminal law. Law enforcement is carried out through a criminal justice system involving police, prosecutors, courts, and correctional institutions. Interaction between subsystems in this system can affect the implementation of their respective duties. In addition, if it is associated with the three legal systems (substance, structure, and legal culture) In addition, it can play a role directly or indirectly to law enforcement officials, which ultimately affect legal protection for child victims of sexual violence.